The Hobbit - Tolkien, JRR (Harper Collins; Film tie-in edition London, 2015)
This is the story of how a Baggins had an adventure, and found himself doing and saying things altogether unexpected... Bilbo Baggins is a hobbit who enjoys a comfortable, unambitious life, rarely traveling further than the pantry of his hobbit-hole in Bag End. But his contentment is disturbed when the wizard, Gandalf, and a company of thirteen dwarves arrive on his doorstep to whisk him away on a journey "there and back again." They have a plot to raid the treasure hoard of Smaug the Magnificent, a large and very dangerous dragon... The prelude to The Lord of the Rings , The Hobbit has sold many millions of copies since its publication in 1937, establishing itself as one of the most beloved and influential books of the twentieth century.